Ruddlesden-Popper-type Nd2-xNi1-yCuyO4±δ layered oxides as candidate materials for MIEC-type ceramic membranes. Issue 12 (September 2020) - Gędziorowski, Bartłomiej; Cichy, Kacper; Niemczyk, Anna; Olszewska, Anna; Zhang, Zijia; Kopeć, Szymon; Zheng, Kun; Marzec, Mateusz; Gajewska, Marta; Du, Zhihong; Zhao, Hailei; Świerczek, Konrad
Highlights: Solid state solution is formed for Ni-rich Nd2-x Ni1-y Cuy O4±δ (x = 0, 0.1) materials. Total oxygen content in Nd2 Ni1-y Cuy O4±δ and Nd1.9 Ni1-y Cuy O4±δ decreases for materials having higher amount of copper introduced. The cation-deficient Nd1.9 Ni0.75 Cu0.25 O4±δ possesses improved electrical conductivity in Ar atmosphere at high temperatures. The A-site deficiency in Nd2-x Ni0.75 Cu0.25 O4±δ enhances bulk diffusion, but hinders surface exchange. CO2 -stable Nd1.9 Ni0.75 Cu0.25 O4±δ membrane with 1.05 mm thickness delivers 0.49 mL cm −2  min −1 oxygen flux at 880 °C. Abstract: Series of Nd2-x Ni1-y Cuy O4±δ Ruddlesden-Popper-type oxides is obtained by auto-combustion synthesis method and systematically characterized concerning phase composition, formation of solid state solution, crystal structure, oxygen content, as well as regarding transport properties and oxygen permeability when applied as mixed conducting ceramic membranes. The A-site deficiency x is discussed in terms of structural stability and its effect on the oxygen content, with ongoing modification of total electrical conductivity observed. In selected Nd2-x Ni0.75 Cu0.25 O4±δ oxides the dominating oxygen defects at high temperatures can be changed from oxygen interstitials to vacancies by the induced A-site deficiency, which affects bulk- and surface-related transport coefficients, as it is observed in electrical conductivity relaxation studies. The optimized Nd1.9 Ni0.75 Cu0.25 O4±δ sinters having increased ionic conductivity, as well as fine, well-sintered microstructure allow to achieve one of the higher reported oxygen fluxes for CO2 -stable Ruddlesden-Popper-based ceramic membranes (e.g. 0.49 mL cm −2  min −1 at ca. 880 °C for 1.05 mm thickness).